2008
DOI: 10.1161/atvbaha.107.151613
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor Receptor-2 Signaling Attenuates Vein Graft Neointima Formation by Promoting Endothelial Recovery

Abstract: Objective-Inflammation appears intricately linked to vein graft arterialization. We have previously shown that tumor necrosis factor (TNF) receptor-1 (TNFR1, p55) signaling augments vein graft neointimal hyperplasia (NH) and remodeling through its effects on vascular smooth muscle cells (SMCs). In this study we examined the role of TNFR2 (p75) signaling in vein graft arterialization. Methods and Results-Inferior vena cava-to-carotid artery interposition grafting was performed between p75Ϫ/Ϫ and congenic (C57B1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 40 publications
2
37
0
Order By: Relevance
“…They also showed that Etk/Bmx, a non-receptor tyrosine kinase, contributed to these results 9) . A previous study observed the anti-apoptotic effect of TNFR2, which specifically activates Etk/ Bmx.…”
Section: Tnf-/gapdhmentioning
confidence: 93%
See 1 more Smart Citation
“…They also showed that Etk/Bmx, a non-receptor tyrosine kinase, contributed to these results 9) . A previous study observed the anti-apoptotic effect of TNFR2, which specifically activates Etk/ Bmx.…”
Section: Tnf-/gapdhmentioning
confidence: 93%
“…Conversely, Zhang et al demonstrated that TNFR1 expression in the arterial wall contributed substantially to atherosclerosis in an arterial grafting model using TNFR1-deficient mice 8) . Furthermore, they demonstrated that TNF signaling via TNFR2 attenuated neointimal hyperplasia by reducing adhesion molecule expression and endothelial cell apoptosis in an arterial grafting model using TNFR2-deficient mice 9) . Xanthoulea et al showed that atherosclerotic plaques are smaller in LDL receptor-deficient mice carrying TNFR1-deficient bone marrow compared to controls 10) .…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis is one of the central mechanisms leading to endothelial dysfunction and results in inflammatory cell infiltration, lipid transport and neointima formation. These alterations induce atherosclerotic lesion rupture and later clinical complications (4)(5)(6). Therefore, inhibiting ECs apoptosis is a promising novel therapeutic option against atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…The cells contributing to this response are predominantly SMCs of medial and adventitial origin. IH occurs both physiologically during development as in the closure of the ductus arteriosus [58], and pathologically as a result of vascular injury [8,22,24,26,48,53,54,. It is thought that AVG IH may be initiated by the abrupt exposure of the veins to the dynamic mechanical environment of the arterial circulation [80].…”
Section: Hyperplasiamentioning
confidence: 99%
“…IH accounts for 20% to 40% of all AVG failures within the first 5 years [13][14][15][16][17]. Several studies have determined that IH develops, to some extent, in all mature AVGs and this is regarded by many as an unavoidable response of the vein to grafting [18][19][20][21][22][23][24][25][26]. IH is characterized by phenotypic modulation, followed by de-adhesion and migration of medial and adventitial smooth muscle cells (SMCs) and myofibroblasts into the intima where they proliferate.…”
mentioning
confidence: 99%